FOREIGN LEXEMES ON SOCIAL MEDIA IN COMMENTS TIKTOK PLATFORM (Scientific journal of the Fergana State University, 2023)
This article examinesnew neologism in social media which based on vocabulary of TikTok comments and translate its meanings in three languages. The purpose of the scientific article is to examine the English language's neologism in comparison to Uzbek and Russian and how it is used among the youngsters, especially generation Z. The article describes those interferences between languages while translating these words to related and non-related family languages.